The 'Art' of Colonisation: Capitalising Sovereign Power and the Ongoing Nature of Primitive Accumulation - Tim Di Muzio (New Political Economy, 2007)
FROM THE ARTICLE: . . . what many critics of the war on terror or US imperialism have so far failed to appreciate is how this project would be impossible without the capitalisation of the state. In this article, I therefore want to suggest that Marx's re-theorisation of the concept of primitive accumulation, combined with a non-Marxist theorisation of state power offered by Jonathan Nitzan and Shimshon Bichler, can help us account for the intimate connection between ongoing primitive accumulation and the capitalisation of the US government. . . . I try to show that we can accept their novel theory of capital as a capitalised and commodified form of power, but argue that the concept of primitive accumulation still has considerable analytical value for theorising the extension and depth of capitalist social property relations within and across political jurisdictions.
Keywords: 330; capitalization; organized violence; primitive accumulation; state